Is estimated intra-operative blood loss a reliable predictor of surgical outcomes in laparoscopic colorectal cancer surgery?. Issue 3 (August 2016) - Saleh, A; Ihedioha, U; Babu, B; Evans, J; Kang, P
Background: Studies have shown that laparoscopic surgery for colorectal cancer is often associated with significantly reduced intra-operative blood loss compared to the corresponding open procedures. Increased intra-operative blood loss can be associated with increased risk of post-operative morbidity and mortality. We sought to determine whether estimated intra-operative blood loss was a reliable predictor of post-operative surgical outcomes. Method: Prospective data were collected for patients undergoing elective laparoscopic colorectal cancer resections from July 2011 to November 2013. Weighing swabs and measuring blood volume in suction devices calculated the estimated intra-operative blood loss. The operative outcome data including post-operative 30 day morbidity and mortality, length of hospital stay, re-admission and re-operation within 30 days were collected. The operative blood loss was grouped into Group 1 (less than 50 ml, Group 2 (50–150 ml) and Group 3 (over 150 ml). Patients who underwent open operations and laparoscopic conversions were excluded. Results: The median age, length of hospital stay, male to female ratio and body mass index were similar in the three groups. There was no 30-day mortality in any of the groups. The number of re-admissions within 30 days was similar in all groups. The re-operation rates within 30 days were higher in Groups 2 and 3 at 11% and 8.6%, respectively. The post-operative complications were 12.5%, 16.7%, and 26% in groups 1, 2 and 3, respectively. There were no anastomotic leaks requiring re-operation noted in Group 3. Discussion: This study has shown that intra-operative blood loss was not associated with increased median length of stay nor did it increase the 30 day re-admission rate. However, increased intra-operative blood loss was associated with increased incidence of post-operative morbidity and risk of reoperation within 30 days.